The Great War in history debates and controversies, 1914 to the present - Winter, Jay 1945-; Prost, Antoine 1933- (Studies in the social and cultural history of modern warfare, 2020)
This revised and updated edition of The Great War in History provides the first survey of historical interpretations of the Great War from 1914 to 2020. It demonstrates how the history of the Great War has now gone global, and how the internet revolution has affected the way we understand the conflict. Jay Winter and Antoine Prost assess not only diplomatic and military studies but also the social and cultural interpretations of the war across academic and popular history, family history, and public history, including at museums, on the stage, on screen, in art, and at sites of memory. They provide a fascinating case study of the practice of history and the first survey of the ways in which the Centenary deepened and deflected both public and professional interpretations of the war. This will be essential reading for scholars and students in history, war studies, European history and international relations